2006
DOI: 10.1186/1477-5751-5-19
|View full text |Cite
|
Sign up to set email alerts
|

Indirect exclusion of four candidate genes for generalized progressive retinal atrophy in several breeds of dogs

Abstract: BackgroundGeneralized progressive retinal atrophy (gPRA) is a hereditary ocular disorder with progressive photoreceptor degeneration in dogs. Four retina-specific genes, ATP binding cassette transporter retina (ABCA4), connexin 36 (CX36), c-mer tyrosin kinase receptor (MERTK) and photoreceptor cell retinol dehydrogenase (RDH12) were investigated in order to identify mutations leading to autosomal recessive (ar) gPRA in 29 breeds of dogs.ResultsMutation screening was performed initially by PCR and single strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The ABCA4 gene encodes ATP-binding cassette, subfamily A, member 4, protein which was described to be an essential protein for human retinal degeneration disease. Moreover, this gene was found as an causal gene associated to generalized PRA disease in different breeds of dogs [36]. Besides, ATP1A, gene comes under Na + /K + transporting ATPase alpha 1 family, has been a causative gene for autosomal recessive cone-rod dystrophy (CORD8) disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…The ABCA4 gene encodes ATP-binding cassette, subfamily A, member 4, protein which was described to be an essential protein for human retinal degeneration disease. Moreover, this gene was found as an causal gene associated to generalized PRA disease in different breeds of dogs [36]. Besides, ATP1A, gene comes under Na + /K + transporting ATPase alpha 1 family, has been a causative gene for autosomal recessive cone-rod dystrophy (CORD8) disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…The canine eye is also comparable in size to the human eye, and dog models have successfully been used for experimental gene therapy for retinal degenerative diseases, such as LCA, RP, and rod-cone dysplasia type 1 (rcd1) [ 12 , 14 , 16 , 62 ]. For over a decade there has been interest in finding a canine model for ABCA4 -mediated diseases [ 23 , 63 , 64 ]. The loss-of-function mutation identified here can be used to develop a large animal model for human STGD.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, these elaborate methods are being replaced by time and cost-effective screening methods. A study investigating ABCA4 in 25 dog breeds affected with PRA identified 18 sequence variants, including a single aa change, by SSCP (Lippmann et al 2006). ABCA4 was excluded as causative gene for PRA in 17 breeds, but could not be assessed in the remainder.…”
Section: Discussionmentioning
confidence: 99%
“…The large size of the ABCA4 coding region and the population structure of the dog that is segregated into genetically isolated breeds (Quignon et al 2007) pose significant limitations for the identification of variations that are potentially important in only a few breeds. Thus, a study excluding ABCA4 from association with various forms of progressive retinal atrophy (PRA), the canine RP homologous group of diseases, in 17 breeds was based on identification of only 18 polymorphisms by SSCP (Lippmann et al 2006). While association studies would be more appropriate for studies of ABCA4 in the dog, these rely on identification and availability of representative markers.…”
Section: Introductionmentioning
confidence: 99%